Fine scale distribution for a population of New Zealand's only endemic dolphin (Cephalorhynchus hectori) shows long‐term stability of coastal hotspots. Issue 1 (24th August 2018) - Brough, Tom; Rayment, William; Slooten, Elisabeth; Dawson, Stephen
Abstract: Marine mammal populations often have "hotspots" of distribution. Understanding what drives these is important for understanding relationships with habitat and evaluating exposure to threats. Few studies investigate the stability of hotspots, yet this information is vital in assessing their importance. In this study, over 9, 000 sightings made during systematic surveys over 29 yr are used to establish the existence, locations, and temporal dynamics of hotspots for Hector's dolphins at Banks Peninsula, New Zealand. Sightings were divided into four seasons and three time periods to assess temporal trends in habitat use. Kernel density analysis was performed on sightings, weighted by survey effort. Density values at hotspots and reference areas were modeled according to season and time period using linear mixed models. Fifty percent of weighted sightings ( n = 4, 513) occurred within 21% of the study area. Hotspots had significantly higher densities during summer and these high‐density areas have remained consistent over time. Such consistency implies importance of these areas to the dolphins' ecology. This information adds to our knowledge of how this endangered species uses its habitat, suggests candidate areas for protection from threats, and provides a baseline for assessing habitat related impacts on Hector's dolphins at Banks Peninsula.© 2018 Society for Marine Mammalogy